Labour market transitions across OECD countries: Stylised facts - Causa, Orsetta (OECD Economics Department Working Papers, 2021)
This paper provides a descriptive analysis of patterns and trends of worker transitions across European countries and the United States, with an emphasis on differences across socio-economic groups. Understanding labour market transitions is important to gauge the scope of labour market reallocation and scarring effects from the COVID-19 crisis. Results of this work show that labour market transitions vary significantly from one country to another and also within countries from one socio-economic group to another. For instance, women are much more likely than men to move in and out of jobs. This reflects the unequal burden of family-related work, which contributes to the higher propensity of women to drop out of the labour force. Zooming in on labour market transitions over the great financial crisis provides an illustration of the long-lasting effects and scarring risks associated with recessions on labour market transitions, especially for young people entering the labour market. The results of this granular analysis inform the policy debate for an efficient and inclusive recovery. While current priorities vary across countries based on economic and social context, one overarching challenge for the recovery is to facilitate hiring dynamics and to minimise long-term unemployment and scarring risks among vulnerable groups who have been hardest hit and face higher risks of scarring from the recession, in particular young people and women